Organizational behavior in an electromechanical sector company from Lima, Peru - Mantilla Gonzales, Daniel (2023)
In the business context, it is necessary to understand employees' organizational behavior for the purpose of development. This study focuses on evaluating the organizational behavior of employees in the industrial company called DIMATIC S.A.C. from Lima, Peru, in order to identify aspects to improve to reduce problems and costs in the organization. To this end, a cross-sectional, descriptive methodological approach was used, by means of a validated questionnaire administered to 58 employees from various departments of the organization. The results showed that 70.69% of employees rated the organizational behavior in the company as "Good". Dimension "Individual" had the highest rating, with 86.21% in the "Good" category. Nevertheless, aspects to improve were identified, especially in terms of stress management, clarity in management, and training promotion. Dimension "Group" was rated as "Good" by 67.24% of respondents. However, the need to improve teamwork, access to information, decision-making and conflict management to promote a collaborative environment became clear. Dimension "Organizational structure" was rated as "Good" by 58.62% of respondents, but the need to strengthen organizational culture, effective communication of values and key practices was identified. As a summary, this study highlights aspects of organizational behavior which demand attention to improve the working environment and the organizational performance of DIMATIC S.A.C.